2015
DOI: 10.1155/2015/328753
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Two School‐Based Programs to Prevent Universal Eating Disorders: Media Literacy and Theatre‐Based Methodology in Spanish Adolescent Boys and Girls

Abstract: Aims. To evaluate the long-term effects of two school-based prevention programs administered to a universal mixed-sex sample of school-going adolescents on disturbed eating attitudes, aesthetic ideal internalization, and other eating disorder risk factors, when compared to a control group. Methods. Participants were 200 adolescents aged 12–15 selected by means of incidental sampling from second-year compulsory secondary education at schools. An interactive multimedia media literacy program (ML + NUT, Media Lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 52 publications
(60 reference statements)
0
15
1
8
Order By: Relevance
“…Furthermore, a moderate temporal stability was observed in self-esteem and the internalization of beauty ideals between 12 and 15 years of age in both genders, pointing to the need to implement prevention programs based on the critique of aesthetic ideals (Espinoza, Penelo, & Raich, 2013; González, Penelo, Gutiérrez, & Raich, 2011; McLean, Paxton, & Wertheim, 2016; Mora et al, 2015) and on strengthening self-esteem for males and females, during early adolescence (Rohde et al, 2015), before the stabilization process of these predictors occurs. Disordered eating shows a moderate temporal stability between 12 and 15 years of age, in both genders.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a moderate temporal stability was observed in self-esteem and the internalization of beauty ideals between 12 and 15 years of age in both genders, pointing to the need to implement prevention programs based on the critique of aesthetic ideals (Espinoza, Penelo, & Raich, 2013; González, Penelo, Gutiérrez, & Raich, 2011; McLean, Paxton, & Wertheim, 2016; Mora et al, 2015) and on strengthening self-esteem for males and females, during early adolescence (Rohde et al, 2015), before the stabilization process of these predictors occurs. Disordered eating shows a moderate temporal stability between 12 and 15 years of age, in both genders.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies that examined the impact of prevention programmes on self-esteem using the Rosenberg questionnaire have reported mixed results. Some studies have found a statistically significant effect at programme conclusion in mixed-gender groups [ 7 , 26 ], as well as in girls-only groups [ 8 , 27 ], while others did not observe change in this outcome [ 28 ]. This difference in outcomes may be due to the difference in the baseline scores.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the effects were found at long-term follow-up (12-30 months). There were, however, inconsistent results for thinideal internalisation whereby the evaluation by Mora et al (2015) found an improvement, but no effect on internalisation was found by Wilksch and Wade (2009) and . Furthermore, thin-ideal internalisation was not assessed by Espinoza et al, despite, as noted above, internalisation being targeted in media literacy interventions.…”
mentioning
confidence: 94%
“…Classroom interventions that have included media literacy components have produced positive outcomes for adolescent girls for weight and shape concern Wilksch and Wade, 2009), body satisfaction (Espinoza et al, 2013) and self-esteem (Mora et al, 2015). Importantly, the effects were found at long-term follow-up (12-30 months).…”
mentioning
confidence: 99%